Gangrene of the buttock/Hemangioma - Bonifazi, E.; Conca, R.; De Roma, M.R. (European Journal of Pediatric Dermatology, 2001)
Two very different disorders such as gangrene of the buttock and hemangioma can affect the buttock of the newborn with very similar clinical features, namely an ischemic patch followed by an ulcer with sharply defined borders. Gangrene of the buttock is a typical disorder of the newborn, due to an artery occlusion in the territory of the hypogastric artery and favored by “inspissatio sanguinis”, vasomotory instability and catheterization of the umbilical vessels. It starts with a white patch that rapidly undergoes necrosis. Later on, the segregation of the latter gives raise to an ulcer. Hemangioma can be preceded by a white ischemic patch, sometimes with central telangiectases. When localized on the buttock, hemangioma can ulcerate, due to soaking of the disposable diaper and rubbing characteristic of the site.